Distribution and molecular characterization of biosurfactant-producing bacteria - Nassir Alyousif; YASIN Y.Y. AL LUAIBI; WIJDAN HUSSEIN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Alyousif NA, Luaibi YYYA, Hussein W. 2020. Distribution and molecular characterization of biosurfactant-producing bacteria. Biodiversitas 21: 4034-4040. Biosurfactants (BSs) are biological surface-active compounds produced by several microorganisms with many areas of application, as such become an important product in biotechnology and consequence to be used in industries. In recent years, many researchers pay attention to BSs producers' microorganisms. The present study was aimed to isolate, identify, and screening BS producing bacteria from six various sites in two different cities in Iraq. Four samples were collected from four sites in Basrah governorate and the rest two samples from Al-Garraf oilfield in Thi-Qar governorate. A total of 33 different bacterial isolates were obtained, 20 out of the 33 were found to be biosurfactants producing isolates that detected through the emulsification index (E24%), oil spreading test, and emulsification activity. The isolated bacterial strains were more identified by 16S rRNA gene sequencing. The results showed that the biosurfactants producing isolates belonged to genera Bacillus, Pseudomonas, Enterobacter, Staphylococcus, Acinetobacter, and Aerococcus. Bacillus jeotgali and Aerococcus viridans are reporting as biosurfactant producing bacteria for the first time and Bacillus jeotgali is isolated for first time from crude oil of oilfield reservoir in this study in world. Moreover, six bacterial isolates were identified as new strains and deposited at NCBI Genbank under accession numbers MT261834 (Bacillus subtilis strain IRQNWYA3), MT261835 (Bacillus licheniformis strain IRQNWYB4), MT261836 (Pseudomonas stutzeri strain IRQNWYF2), MT261837 (Pseudomonas zhaodongensis strain IRQNWYF3), MT261838 (Pseudomonas sp. IRQNWYF4) and MT261839 (Bacillus licheniformis strain IRQNWYF5). A2 isolate that was identified as Pseudomonas aeruginosa has shown the highest values of emulsification activity and emulsification index (1.678±0.050 absorbance at 540 nm and 56.6% respectively) that show efficient potential of biosurfactant production. Phylogenetic tree was also constructed in this study based on 16S rRNA gene sequences of biosurfactant-producing bacteria to evaluate their close relationship and evolution between them.